Effect of nursing behaviour, sex of the calf, and parity order on milk production of buffaloes - Oliveira, Aparecida de F. M.; Quirino, Celia R.; Bastos, Rosemary (Revista Colombiana de Ciencias Pecuarias, 2017)
Background: the allonursing effect on daily milk production (DMP) and total milk production (TMP) has been little explored. Objective: to evaluate the effect of nursing behaviour, sex of the calf and parity order (PO) on DMP and TMP of buffalo cows. Methods: thirty-five buffalo cows and their calves were evaluated. Observations were performed monthly (three consecutive days) from May to November. The nursing behavior was characterized as: 1) isolated filial nursing (IFN); 2) collective filial nursing (CFN), and 3) non-filial nursing (NFN). Cows were grouped into four categories to study the effects of nursing behavior on DMP and TMP: 1) non-permissive (NP); 2) filial permissive (FP); 3) filial and collective filial permissive (FCFP); and 4) filial, collective filial and non-filial permissive (FCFNFP). DMP was recorded three days per month and TMP was calculated as DMP*270 days of lactation. Results: sex of the calf and second and third PO had an effect on nursing behavior (p<0.05). DMP and TMP were significantly affected by calf sex and nursing behaviour (p<0.05). PO had no effect on DMP and TMP. Conclusion: our results suggest that nursing behaviour is associated with milk production in buffalo cows. Buffalo cows that accept all types of nursing behaviour had the highest DMP and TMP. Sex of the calf influenced nursing behaviour, DMP, and TMP, so that buffalo cows with male calves displayed more frequent allonursing behaviour and yielded more milk.